ANALISIS IMPLEMENTASI PRODUK PEMBIAYAAN AMANAH PADA PENGADAIAN SYARIAH UNIT PASAR SEKETENG - Nining Sudiyarti; I Ismawati; Lara Okta Yusmanti; Wahyu Haryadi (Fakultas Ekonomi dan Manajemen, 2021)
This study aims to know the implementation and factors influenced the implementation of Amanah financing products at syariah pawnshop unit of Seketeng market. Type of this study was descriptive, which is a study that aims to describe a symptom or condition without connecting or comparing with other variables. The data used was qualitative data in the form of informants’ answer related to the object of study obtained through interviews. The informants in this study consisted of key informants, namely the head of the syariah pawnshop unit of seketeng market and the main informants, namely the pawnshop employees or special customers of trust financing product with the number of informants were 5 informants. Data were analyzed using qualitative data analysis techniques of Miles and Huberman which consisted of data collection, data reduction, data presentation and conclusion/verification. The results of study showed that the implementation of amanah financing products at syariah pawnshop unit of Seketeng Market used the ijarah vomitiyah bi tamlik (IMBT) financing system, which is buying and selling activities in the form of service leases that end with transfer of ownership. The pawnshop will sell certain items to customers on credit with a guarantee, the guarantee will remain in the pawnshop during the installment payment process. The problems in implementing it was the ineffective billing process so that the installment payment process by customers did not run optimally. The solution that could be done was by optimizing the process of analyzing prospective customers prior to acceptance.